“Análisis del bienestar animal y su efecto en la calidad de la carne de cerdo” - Chica Cruz, Mariuxi Roxana (2023)
This document detailed information regarding the analysis of animal welfare and its effect on the quality of pork, so that the animal obtains good nutrition, reproduction and management to favor producers and increase their economic gain. It was elaborated through the bibliographic information or compilation of virtual libraries, updated texts, magazines and articles, presentations, congresses and all bibliographic material of a scientific nature, which was submitted to processes of analysis, synthesis and summary. The conclusions determined that pig producers are currently concerned about the welfare of animals, in order to produce good quality meat, which improves their economic income; pigs are raised in suitable environments, allowing them to reduce stress, where producers invest in everything necessary to avoid production losses and pigs are beings who feel pain, joy and pleasure, therefore it is necessary to carry out good management during throughout their growth stage, from their arrival (assessing their state of health and organizing it within their pens), maintenance of the sheds (cleanliness and adequate substrate), adequate density (adequate surface so that they do not feel discomfort), food management ( balanced diets), thermal comfort (without heat or cold), health care (vaccination schedule, medicines, constant medical evaluation), performance which will culminate in the slaughter stage; a good handling will result in a good quality meat, with excellent consumption, which will allow the increase of the economic income of the pig producers.